Produção de etanol 2G e biogás utilizando resíduos da cultura da soja - Vedovatto, Felipe (2021)
Lignocellulosic biomass residues are an alternative to the second-generation ethanol (2G) and biogas production, due to their chemical composition (cellulose, hemicelluloses, and lignin), because it is a renewable resource, low cost, and not compete with food crops. These residues come from agriculture and agroindustry. Subcritical water hydrolysis of lignocellulosic biomass is an alternative for obtaining fermentable sugars to produce biofuels. Therefore, the present paper aims to evaluate the subcritical water hydrolysis of soybean residues (straw and hull) for obtaining fermentable sugars and biofuels production (ethanol and biogas). The work was organized in three stages. In stage 1, the obtaining, characterized, and prepared soybean straw and the hull were performed. In stage 2, the assays of subcritical water hydrolysis were conducted. The experimental conditions investigated were the temperature (180, 220 e 260 °C) and liquid-solid mass ratio (9 g and 18 g water/g straw and 7.5 g and 15 g water/g hull). The time of hydrolysis reaction was 15 min with a set pressure at Mpa. The reducing sugars yield, efficiency, composition of hydrolysates, and the residues after hydrolysis were evaluated. In stage 3, was performed evaluating ethanol production using the yeast Wickerhamomyces sp. and the condition of higher reducing sugars yield. At this stage, the biochemical biogas and methane potential of new residues, hydrolysates, and fermented hydrolysates by anaerobic co-digestion were performed. Subcritical water hydrolysis provided the obtaining fermentable sugars. The conditions of 220 °C/R-18 e 220 °C/R-15 provided higher reducing sugars yield with 9.56 ± 0.53 g/100 g straw and 10.15 ± 0.50 g/100 g hull at 4 min and 3 min of the hydrolysis reaction, respectively. The efficiency of hydrolysis for both residues was approximately 23 g/100 g carbohydrates. The ethanol production was 5.57 ± 0.01 g/L e 6.11 ± 0,11 g/L ethanol for straw and hull hydrolysates diluted and supplemented with glucose (10 g/L). The maximum ethanol production in a bioreactor for straw and hull hydrolysates without changing the pH was 48 h and with changing the pH was 24 h. The biochemical biogas and methane potential were possible for new residues, hydrolysates, and fermented hydrolysates. Highlighting the biogas production of 739 ± 37 e 652 ± 34 NmL/gVSad for straw hydrolysates fermented with and without changing the pH and 620 ± 26 NmL/gVSad for hull hydrolysate fermented without changing the pH. Given these results, it is concluded that the soybean residues combined with the subcritical water hydrolysis process, ethanol production process, and anaerobic co-digestion have the potential for renewable energy production.